Relation between extent of coronary artery disease and severity of hyperlipoproteinaemia. Issue 12 (December 1975) - Murray, R G; Tweddel, A; Third, J L; Hutton, I; Hillis, W S; Lorimer, A R; Lawrie, T D
Abstract : Lipoprotein analyses were performed in 133 male patients and were correlated with the coronary arteriographic findings. The prevalence of hyperlipoproteinaemia was significantly higher in those patients with coronary artery disease (P less than 0-02). In addition, the more extensive the degree of coronary artery pathology the higher were the plasma concentrations of total cholesterol, triglyceride, and low density lipoprotein (LDL) cholesterol. Hyperlipoproteinaemia was more prevalent in the younger patients with coronary artery disease (P less than 0-02).